Profile of Hand Surgery Cases at Kirtipur Hospital - Karki, Bishal; Nakarmi, Kiran; Magar, Mangal Gharti; Nagarkoti, Krishna; Rai, Shankar Man (Journal of Nepalgunj Medical College, 2018)
Background: There can be multiple hand problems with which patients can present. Such hand problems can be because of any kind of trauma, birth defects, tumours, infection or other conditions. Hand surgery is a special field of plastic surgery, which deals with these hand problems. The Department of Burns, Plastic & Reconstructive Surgery of Kirtipur Hospital run by Public Health Concern Trust-Nepal has been providing hand surgery service to the patients with these hand problems. Aim of Study: To analyse the various types of surgical hand problems in patients attending Kirtipur Hospital. Material and Methods: It is a cross sectional retrospective observational study of the patients with different hand problems done at the Department of Burns, Plastic & Reconstructive surgery of Kirtipur Hospital from January to December 2016. Results: There were 124 patients who presented with various hand problems. There was male preponderance and the most common age group affected was between 15-60 years. Hand trauma was the most common cause of hand problems followed by post burn contractures. Conclusion: Hand is a complicated organ which can give rise to various problems. Hand surgery is an essential component of reconstructive surgery to deal with these problems. JNGMC, Vol. 14 No. 2 December 2016, Page: 41-43